Mapping substrate use across a permafrost thaw gradient. (December 2022) - Fofana, Aminata; Anderson, Darya; McCalley, Carmody K.; Hodgkins, Suzanne; Wilson, Rachel M.; Cronin, Dylan; Raab, Nicole; Torabi, Mohammad; Varner, Ruth K.; Crill, Patrick; Saleska, Scott R.; Chanton, Jeffrey P.; et al.
Abstract: Permafrost thaw in northern peatlands is likely to create a positive feedback to climate change, as microbes transform soil carbon (C) into carbon dioxide (CO2 ) or methane (CH4 ). While the microbiome's encoded C-processing potential changes with thaw, the impact on substrate utilization and gas emissions is less well characterized. We therefore examined microbial C-cycling dynamics from a partially thawed Sphagnum -dominated bog to a fully thawed sedge-dominated fen in Stordalen Mire (68.35°N, 19.05°E), Sweden. We profiled C substrate utilization diversity and extent by Biolog Ecoplates™, then tested substrate-specific hypotheses by targeted additions (of glucose, the short chain fatty acids (SCFAs) acetate and butyrate, and the organic acids galacturonic acid and p-hydroxybenzoic acid, all at field-relevant concentrations) under anaerobic conditions at 15 °C. In parallel we characterized microbiomes (via 16S rRNA amplicon sequencing and quantitative polymerase chain reaction) and C gas emissions. The fen exhibited a higher substrate use diversity and faster rate of overall substrate utilization than in the bog, based on Biolog Ecoplate™ incubations. Simple glucose additions (akin to a positive control) to peat microcosms fueled fermentation as expected (reflected in enriched fermenter lineages, their inferred metabolisms, and CO2 production), but also showed potential priming of anaerobic phenol degradation in the bog. Addition of SCFAs to bog and fen produced the least change in lineages and in CO2, and modest suppression of CH4 primarily in the fen, attributed to inhibition. Addition of both organic acids greatly increased the CO2 :CH4 ratio in the deep peats but had distinct individual gas dynamics and impacts on microbiota. Both organic acids appeared to act as both C source and as a microbial inhibitor, with galacturonic acid also likely playing a role in electron transfer or acceptance. Collectively, these results support the importance of aboveground-belowground linkages - and in particular the role of Sphagnum spp.- in supplying substrates and inhibitors that drive microbiome assembly and C processing in these dynamically changing systems. In addition, they highlight an important temporal dynamic: responses on the short time scale of incubations (which would reflect transition conditions in the field) differ from those evident at the longer scales of habitat transition, in ways consequential to C gas emissions. In the short term, substrate addition response reflected microbiome legacy (e.g., bog communities were slower to process C and better tolerated inhibitors than fen communities) but led to little overall increase in C gas production (and a high skew to CO2 ). At the longer time scale of bog and fen thaw stages (which are used to represent these systems in models) the concomitant shifts in plants, hydrology and microbiota attenuate microbiome legacy impacts on substrate processing and C gas emissions over time. As habitat transition areas expand under accelerating change, we hypothesize an increased role of microbiome legacy in the landscape overall, leading to a lag in the increase of CH4 emissions expected from fen expansion. Highlights: Microbiome legacy underlies bog vs. fen differences in response to substrate addition Microcosm substrate dynamics reflect short-term habitat thaw transitions Organic Sphagnum acids strongly impact microbiota and carbon emissions